Health effects of wind turbine noise and road traffic noise on people living near wind turbines. (April 2022) - Radun, Jenni; Maula, Henna; Saarinen, Pekka; Keränen, Jukka; Alakoivu, Reijo; Hongisto, Valtteri
Abstract: Very few surveys have investigated the health effects of both wind farms and road traffic so that the public health effects of environmental stressors are broadly understood. This case-control study examined the influences of both wind turbine noise and road traffic noise on self-reported symptoms and diseases close to wind turbines and in a control area. Wind turbine sound levels 17–39 dB L Aeq met new national regulation (40 dB). Daytime road traffic noise levels were 32.5–63.5 dB, sometimes exceeding the regulation (55 dB). Altogether 676 residents responded to a masked living environment questionnaire. Higher wind turbine sound level was only associated with more likely reporting wind turbine noise annoyance and not with reporting of other symptoms or chronic diseases. On the other hand, higher road traffic sound level was associated with increased odds for road traffic noise annoyance, migraine or headache, dizziness, impaired hearing, pressure in ears, tachycardia or heart palpitations, and heart disease. Road traffic exposure seems to deserve attention especially if daytime levels exceed 55 dB. The health effects of wind farms seem to be limited to noise annoyance in areas where all residents are exposed to sound levels under 40 dB. Highlights: The health effects of both wind turbine noise and road traffic noise were examined. The survey involved a group living close to turbines and a control group far away. Wind turbine noise level was only associated with higher noise annoyance. Road traffic noise level was related both to annoyance and various health effects. Road traffic noise can be larger health risk in wind turbine areas than turbines.